Teacher participatory decision-making in schools: A pre-requisite for democratic governance in Ghanaian second cycle educational institutions - Aboagye, Gabriel Kwesi; Ahmed, Hassana (Journal of Educational Development and Practice, 2019)
Participatory decision-making in schools has been identified as a key tool for improving teachers* professional development. However, not much has been done in terms of scientific research to find out the nature, level and areas of teacher participation in making school decisions. Therefore, this study sought to establish the areas and ways of involving Senior High School teachers in decision-making in schools in the Mampong Municipality. The descriptive survey design was adopted for the study. The purposive and stratified sampling techniques were adopted to select the participants for the study. Questionnaires were used to collect data from 252 randomly selected professional teachers. It was observed from the study that teachers were always involved in curriculum and instructional activities and occasionally engaged in school operational activities and decisions that promoted school-community relationship. However, teachers were never involved in decision making on student admission and placement, staffing and financial matters. Teachers were involved in school decision-making through delegation, school meeting, school Board of Governors, and school committee systems. It is, therefore, recommended that the heads of schools should decentralise decision-making in their schools to allow greater teachers’ involvement in decision-making.